(untitled) (Revista Paradigma, 2020)
This article intends to analyze the exercise of the jurisdiction by the State through the perspective of the public services, conceptualizing both of them with optics permeated by the notion that the State’s power functions written in the article 2nd from the Federal Constitution of 1988 aren’t incommunicable, but are in constant interaction, and that the borders between their typical and atypical activities don’t reveal themselves as exactly or objectively outlined. On a second moment, it intends to explore the relation established between the jurisdictional activity and the public services, that dislocate themselves from the context of public administration, to the Judiciary. The research method employed was the bibliographic research.